Pengaruh Konten Media Sosial terhadap Perilaku Fear of Missing Out (FOMO) untuk meningkatkan Konsumerisme pada Generasi Z - Zaki Rahman Putra; Nur Hayati (PAPSEL Research and Consulting, 2025)
This research discusses the influence of social media content on the emergence of Fear of Missing Out (FOMO) behavior and its connection to increasing consumerism in Generation Z. This generation grew up in a digital ecosystem saturated with visualizations of ideal lifestyles disseminated through platforms like TikTok, Instagram, and Twitter. Constant exposure to such content creates anxiety about missing out on seemingly important social experiences. FOMO then triggers consumptive actions, not due to functional needs, but because of symbolic impulses and social pressure to remain relevant within digital communities. This study employs a descriptive qualitative method with in-depth interviews of informants aged 20–26 years. The analysis results show that content such as unboxing, product reviews, and personal lifestyles have a significant impact on creating social pressure and shaping consumption-based identity. These findings underscore the importance of digital literacy and critical awareness so that Generation Z does not get trapped in a cycle of impulsive consumption, which poses risks to both mental and financial health. As an alternative, the Joy of Missing Out (JOMO) approach is introduced to build healthier and more authentic digital relationships.